Proposals for risk management in environments with activities involving nanomaterials - Luís Renato Balbão Andrade; Fernando Gonçalves Amaral; William Waissmann (Fundação Oswaldo Cruz (FIOCRUZ), 2013)
The handling of nanomaterials presents enormous challenges for risk management in research and production of new materials. However, data on the impacts of these new materials on human health and the environment need to be expanded. Several efforts have been made to mitigate the hardships and offer guidelines for the management of risks associated with nanomaterials. This article aims to provide a broad and comparing view of the main proposals in the literature. The methodology was systematic analysis encompassing 17 proposed risk management with nanomaterials. The results indicate that, although there is no consensus on the metrics used to characterize the risks of na-nomaterials, the adoption of the Precautionary Principle, the control banding approach and stakeholder involvement stands out among the documents analyzed.